STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI TANJUNG WOKA KABUPATEN BOLAANG MONGONDOW TIMUR (Destination Development Strategy of Tanjung Woka Beach, East Bolaang Mongondow Regency) - Egi Dea Bukoi; Ribka Magdalena Kumaat; Grace Adonia Josefina Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to formulate a strategy for developing a tourist destination in Tanjung Woka Beach, Bolaang Mongondow Timur Regency. The study was conducted from January 2020 to May 2020. The sampling method in this study is purposive sampling. The data used in this study are primary data and secondary data. Primary data obtained from direct interviews with respondents, while secondary data were obtained from the internet and related agencies. The data analysis method used in this study is the SWOT analysis. The research result showed that based on the SWOT analysis, the strategy for developing tourist destinations for Tanjung Woka Beach is in quadrant 1, which means that a strategy is needed that supports the strengths and takes advantage of the various opportunities that exist.